Cover Picture: Proton‐Exchange Rates on Hydroxide Bridges of Mineral‐Like Metal‐Hydroxide Clusters (ChemistrySelect 6/2016). Issue 6 (29th April 2016) - Fields, Caitlyn R.; Oliveri, Anna F.; Colla, Christopher A.; Johnson, Darren W.; Casey, William H.
Abstract : The cover picture shows an artist's rendition of proton exchange between metal‐bridging oxygen atoms and water molecules at the surface of a mineral‐like cluster ion. The artist depicts metal ions as purple spheres, oxygen atoms as blue spheres and protons as white spheres. Red arrows indicate the motion of exchange. More information, including quantitative measures of the exchange rates, can be found in the Communication by Darren W. Johnson, William H. Casey, et al. (DOI:10.1002/slct.201600190 ). (Artist: Anna F. Oliveri)